The Transformation Of Digital Public Service Governance In Indonesia: An Analysis Of Policy Implementation From A Public Administration Perspective - Imam Syafi'i (International Journal of Social Sciences, Language, and Education, 2026)
This study investigates the policy implementation of digital public service governance in Indonesia through a non-empirical library research design anchored in public administration theory. By synthesizing peer-reviewed literature, statutory regulations, and official institutional reports, the research evaluates the interplay between legislative mandates, bureaucratic restructuring, and organizational adaptation. The findings indicate that while national regulatory frameworks provide essential legal certainty, successful digital transformation is critically dependent on overcoming structural inertia and fostering inter-agency synergy. Furthermore, the analysis highlights that digital literacy and strategic leadership serve as vital determinants for bridging the gap between policy design and grassroots execution. Ultimately, this study contributes to the broader discourse on public sector modernization by demonstrating that technological integration must be accompanied by comprehensive cultural shifts within state institutions to achieve sustainable administrative efficiency and enhanced public service delivery.